ANALISIS KOMPARATIF PENGARUH RISIKO KREDIT TERHADAP PROFITABILITAS BANK UMUM KONVENSIONAL DAN BANK UMUM SYARIAH - Enok Nurhayati; Wawan Ichwanudin; Nindy Septia Permatasari (FEB Universitas Sultan Ageng Tirtayasa, 2016)
The objective of this research was to compare the Conventional Banks and Islamic Banks and Credit Risk influence on the profitability of Conventional Banks and Islamic Banks on 2004-2012 Period. The independent variables in this researchare Non Performing Loan (NPL) and Loan to Deposit Ratio (LDR) for conventional banks and Non Perfoming Financing (NPF) and Financing to Deposit Ratio (FDR) for Islamic bankswhile the dependent variable is Return on Assets (ROA). The researcher used in this study is a method of quantitative comparative and associative.While the methods of analysis used are multiple linear regression analysis, t test, coefficient of determination and Chow test. From the test results of hypothesis was performed by using the t test,the results as follows: The result show Ha1is rejected, it means there were no significant negative influences between the NPL to the ROA. The Ha2is accepted,tt means partially there were significant negative effect between LDR to the ROA. While the test result of Ha3is rejected,it means there were no significant negative influences between the NPF to the ROA. And the test resultof Ha4showno significant positive influences between the FDR to the ROA. For the results of the Chow test showthat the Ha5is accepted, which means there is a difference between conventional banks and Islamic banks.Key words: NPL, LDR, NPF, FDR and ROA